Gebrakan dan Penganekaragaman: Budaya Persaingan dalam Pertumbuhan Seni Pertunjukan Rakyat di Boyolali Jawa Tengah - Kiswanto Kiswanto; Tri Joko; Aris Dwiyanto (Universitas Gadjah Mada, 2021)
This study aims to reveal and explain the cultural practice of competition in the growth of folk performing arts in Boyolali through the monopolistic competition theory approach of Edward Hastings Chamberlin, which has been adapted and developed critically with ethnographic research methods. This research produces findings in the form of a cultural pattern of competition that occurs indirectly among folk performing arts communities in Boyolali. Its characteristics can be recognized by the pattern of development and diversification of works of art between communities which is carried out by adding and producing forms of art that are distinguished from one another. This pattern is built through the process and the result of creativity from the practice of developing, creating, and/or adopting art forms based on the intention to create and present a gebrakan. On the other hand, this process is also part of the diversification process carried out as a strategy to strengthen the community’s positioning in facing market competition. The patterns and strategies developed in it have had a positive impact on the growth of folk performing arts which are increasingly diverse, so that there are many choices of competing art forms that can be chosen to be seen or ordered to be performed.